2014
DOI: 10.1007/s11695-014-1238-6
|View full text |Cite
|
Sign up to set email alerts
|

The Gender-Related Differences of Nutrient Intakes in a Group of Italian Obese Patients Display the Ongoing Transition from Mediterranean to Western Dietary Patterns

Abstract: The consumption of high-protein foods in both sexes, and even more the association with high-simple carbohydrate foods in women, display the Westernization of traditional eating habits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
3
7
0
Order By: Relevance
“…Moreover, women recorded a more regular use of fruit, vegetables and legumes, and a less frequent use of soft drinks, meat, pasta, and wine than men. These findings are in accordance with previous studies in Italy, indicating that animal protein intake is higher in men [ 44 ] than in women, who also consume fruit and vegetables more regularly [ 45 ]. A low adherence to the MD in men has been previously reported and correlated with markers of atherosclerosis and cardiovascular risk [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, women recorded a more regular use of fruit, vegetables and legumes, and a less frequent use of soft drinks, meat, pasta, and wine than men. These findings are in accordance with previous studies in Italy, indicating that animal protein intake is higher in men [ 44 ] than in women, who also consume fruit and vegetables more regularly [ 45 ]. A low adherence to the MD in men has been previously reported and correlated with markers of atherosclerosis and cardiovascular risk [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, our study highlighted a considerable consumption of animal protein. This aspect clearly suggests a trend away from traditional Mediterranean eating towards Western dietary habits, in agreement with previous reports [8,[16][17]. Moreover, the ω-6 fatty acid intake exceeded the RDA by 60%.…”
Section: Discussionsupporting
confidence: 92%
“…Ranging from 2 to 4, the score is associated with an odds ratio of 17 to predict liver fibrosis, with a negative predicted value close to 100% [4,5]. Although inadequate dietary habits in obesity are strongly related to the development of insulin resistance and liver dysfunction [6], few investigations have focused on the dietary habits in obese Italian subjects with the quantitative determination of nutrient intakes, and the relationships between dietary constituents and the development or progression of metabolic and liver disorders in obesity [7,8]. The aims of this study were to investigate the following aspects in an Italian group of obese patients: the prevalence of IR and positive BARD (score ≄2); the nutrient intakes by quantitative determination; the evaluation of the excessive or deficient, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However the use of dietary pattern analysis is necessary to identify the whole diet effects on health outcomes; since this multivariate approach could resolve concerns about potentially antagonistic and interactive effects among nutrients and foods (2). Most previous studies on adult dietary patterns indicated that dietary patterns including fresh fruits and vegetables, legumes, milk, and milk products were associated with lower general and central obesity (3-5). Conversely, dietary patterns containing high fats, oils, sweets, refined meats and red meats were associated with obesity (6, 7).…”
Section: Introductionmentioning
confidence: 99%